Effects of infill pattern and density on wear performance of FDM-printed acrylonitrile- butadiene-styrene parts - Karabeyoglu, Sencer Sureyya; Eksi, Olcay; Yaman, Pasa; Kucukyildirim, Bedri Onur (WALTER DE GRUYTER GMBH, 2021)
Acrylonitrile-butadiene-styrene test specimens were additively manufactured by fused deposition method to investigate the effects of infill pattern and density on wear rate, coefficient of friction, wear mechanisms, and microscopic wear characterization. The surface morphology of specimens was characterized using a scanning electron microscope. Under constant parameters of applied load, sliding speed, and sliding time, wear tests were carried out at room temperature. The study revealed that a grid pattern of high infill density and a honeycomb pattern of low infill density showed the lowest wear rate and lowest coefficient of friction compared to the rectilinear pattern. Infill pattern and density affected the wear rate behavior of specimens directly. Moreover, adhesion between additively manufactured layers along with surface texture affects the wear behavior and wear rate. Increasing infill density allowed poor cooling of previously built layers. Longer process time results in rough surfaces.
Keywords: ABS; FDM; infill density; infill pattern; wear; BEHAVIOR; Polymer Science